Study on Comparative Analysis of Rising Non Performing Assets of Bank of Maharashtra and ICICI Bank - Nilesh R. Kharche; Ushmita Gupta (Eduvest - Journal of Universal Studies, 2023)
The banking industry plays a crucial role in the financial and economic growth of a country. A well-functioning banking sector acts as a catalyst in achieving rapid economic development by providing a stable financial system, mobilizing savings, channeling funds to productive sectors, facilitating transactions, and supporting monetary policy. However, one challenge that banks face is the issue of Non-Performing Assets (NPA), which refers to loans that are not repaid by borrowers as per the agreed terms. In conclusion, high levels of NPAs can have several limitations on the banking sector and the economy, including reduced incomes, unrecoverable principal amounts, negative indicators, operational inefficiency, political interference, and constraints on financing for certain sectors. Effective management of NPAs is crucial for maintaining a healthy banking sector and supporting sustainable economic growth. The present comparative study is aim to know NPAs of Bank of Maharashtra(BOM) and ICICI bank the study applied quantitative research method. In this paper, the NPAs of public and private sector banks in India has been compared over a period of last five financial years. It has been observed that the percentage of net NPAs to net advances in public sector banks is varied between 3.1-0.9. In case of private sector banks, it varied between 2.4-0.4. The collected data is analyzed using descriptive analysis, chi square test, etc. This study also identifies the cause of the increasing non-performing assets in the banks and a few suggestions.